Structure, Function, and Regulation of Molecules Involved in Leukocyte Adhesion Proceedings of the Second International Conference on: "Structure and Function of Molecules Involved in Leukocyte Adhesion II" - Lipsky, Peter E.; Rothlein, Robert; Kishimoto, Takashi Kei; Faanes, Ronald B. (Springer New York, 1993)
Leukocyte adhesion molecules have been the subject of intense basic and preclinical research. Results from clinical trials obtained sofar with antibodies directed towards these surface proteins offer promise for the prevention of graft rejection and effective treatment of acute and chronic inflammatory disease. This volume presents a comprehensive review of contemporary research on the structure, function and regulation of leukocyte adhesion molecules and their ligands, from the molecular to the clinical level. The blend of basic science and clinical applications presented in Structure, Function and Regulation of Molecules Involved in Leukocyte Adhesion provides clear evidence of the biological importance of cell-cell interactions and the many potential clinical dividends afforded by understanding the molecular basis of cell adhesion. It will appeal to a broad range of readers in immunology and cell biology
Keywords: Infectious Diseases; Cell Biology; Biochemistry, general; Immunology; Emerging infectious diseases; Cytology; Biochemistry; Leukozytenadhäsion; Regulation; Aufsatzsammlung; Konferenzschrift -- 1991 -- Titisee-Neustadt